Challenges and perceptions of dental undergraduate students regarding active learning in clinical practice: A qualitative study - Maria de Lara Araújo Rodrigues; Bruna Navarro Camargo da Silva; Marcella Alves dos Anjos; Eduarda Betiati Menegazzo; Álex Moreira Herval; Luciane Miranda Guerra; Jaqueline Vilela Bulgareli (PLoS ONE, 2025)
Objectives This study aimed to investigate the challenges faced by dental students during clinical practice and to understand their perceptions of how active learning methodologies contribute to fostering critical and reflective participation in problem-solving throughout the teaching-learning process. Methods This qualitative study applied the action research method in a descriptive and interpretive manner, implementing active learning methodologies in the adolescent clinic of the Federal University of Uberlândia (Brazil). This clinic is among the fundamental elements in the Public Health System. This research included 33 students in the final term of the dentistry course (10th term), divided into three groups of 9–13 students each, and regularly enrolled in clinic practice. The data was collected in three 90-minute workshops with each group. This study used Minayo’s methodological framework and the arc method by Spanish educator Charles Maguerez to conduct the action research. This research comprised five steps: 1. Clinical experience; 2. Identification of challenges; 3. Theorization of challenges based on scientific evidence; 4. Development of action strategies; 5. Application of strategies in clinical practice. The theoretical framework was Paulo Freire’s problematization methodology. Data analysis followed the thematic content analysis technique. Results After comprehensive data analysis, the main challenges concerned the work process, productivity, and infrastructure. The formulated strategies included the establishment of a procedures table, implementation of minimum age regulations for companions in the waiting area, adjustment of clinic hours, enhancement of auxiliary professional training, and maintenance of dental equipment. Conclusion The groups’ experience with active methods qualified them to identify and address relevant practice challenges. It allowed study participants to lead their teaching-learning process and develop action strategies to transform the work process. Reflecting on implementing these strategies in clinical practice transformed the students’ reality and promoted more dynamic and meaningful learning. However, solving challenges, such as infrastructure, requires a continuous commitment of financial resources and institutional support.